Fully coupled electrothermal and mechanical simulation of the production of complex shapes by spark plasma sintering. Issue 7 (July 2021) - Van der Laan, A.; Epherre, R.; Chevallier, G.; Beynet, Y.; Weibel, A.; Estournès, C.
Abstract: The obtention of an accurate mechanical model of the spark plasma sintering (SPS) requires the identification of creep parameters. Those parameters are usually determined experimentally, which involves several tests and could be a source of error for the model predictions. A numerical identification, based on only one SPS experiment per material, allowed the determination of the creep parameters of Al2 O3 and TiAl samples. The resulting mechanical model was then coupled with an electro-thermal model of the system to obtain a fully coupled simulation of the SPS. This model can predict the densification behavior not only of simple pellets, but also of complex shape configurations. It accurately predicts the density gradients inside the complex sintered parts as well as the interface distortion during sintering. Thus, numerical simulation can be used as an efficient predictive tool to obtain fully dense objects with the desired geometry.